PENGARUH KOLABORASI WANITA PENGUSAHA SKINCARE BERBASIS E-COMMERCE - Nynys Maharani; Titis Tatasari; Revangga Aleandro Safirulloh Azhary; Hanna Halimah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In Indonesia in 2045 getting a demographic bonus, 70% of Indonesia's population will reach productive age. Skincare is an item that can attract the important role of women entrepreneurs in developing e-commerce businesses, especially in the beauty field. Collaboration with e-commerce media platforms is important to determine sales decisions to consumers.This research aims to see the influence of collaboration between women skincare entrepreneurs based on e-commerce. The method used in this research is descriptive qualitative method, namely by combining the results of analyzing several research journals, books, and sources from the internet that successfully do business through the e-commerce platform media. The results showed that with the e-commerce platform media, women entrepreneurs can increase their productivity by building a strong business and expanding their market reach for both men and women. This research is expected to provide useful insights for readers about women skincare entrepreneurs in doing e-commerce business.